The Non-Observed Economy in Morocco: Estimation and Analysis Using the Currency Demand Approach: L'économie non observée au Maroc: estimation et analyse à l'aide de l'approche de la demande de monnaie - Kawtar, EL AIDA; Ithri, FETTAHI (African Scientific Journal, 2021)
Abstract This study estimates the size of the non-observed economy (NOE) in Morocco and analyzes its evolution over the period 1977 - 2019. We estimate a currency demand function following Tanzi’s (1980; 1983) Currency Demand Method. We take into consideration the difference in money velocities between the formal and informal sectors using the Ahumada et al.’s (2006) correction. We also adopt the fully modified least squares (FM-OLS) in order to tackle the series’ cointegration and to circumvent the serial autocorrelation issues. In terms of epistemological paradigms, we follow the positivism stance with a hypothetico-deductive approach. In addition to the conventional variables used in the currency demand approach, we emphasize the effects of other variables that are specific to the Moroccan context and that influence the size of its informal economy. Therefore, we introduce a dummy variable that captures the impact of banking regulations, net remittances, consumer price index, the part of government’s final public consumption in the Gross Domestic Product (GDP) and the part of public investment in GDP. The results of our econometric estimations show that remittances have a negative effect on currency demand. The weight of taxation, reforms, rising living costs, the part of wages in the national revenue, the consumer price index and the parts of public consumption and investment in GDP have a positive impact on the quantity of currency circulating in the economy. Keywords: Non-observed economy, informal sector, tax burden, fiscal evasion, money velocity currency demand method, fully modified least squares.